Fundamentals of Rural Marketing - (:unkn) unknown (ATLAS SkillTech University, 2025)
TYBBA Fundamentals of Rural Marketing Question Paper Semester 6
25BB605MRF
Third Year Question Paper
Keywords: Fundamentals of Rural Marketing; Rural Marketing; Marketing